PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP EMPLOYEE SATISFACTION YANG DIMEDIASI OLEH CITRA PERUSAHAAN - Fauzi, Adilla Nanda Citra; W, Wahidahwati (Fakultas Ekonomi, Universitas Cenderawasih, 2019)
This research aims to examine the effect of corporate social responsibility on the employees’satisfaction which was mediated by company image. The research was quantitative with a survey asthe instrument and used questionnaires in data sampling. In line with, the data collection techniqueused convenience sampling, in which the sample was based on element existence and easiness tohave it. Moreover, the sample was 100 respondents of employees of PT PJB UP Gresik. In addition,the data analysis technique used Structural Equation Modeling (SEM) with SmartPLS 3.0.The research result concluded that corporate social responsibility had a positive effect on theemployees’ satisfaction and company image. Furthermore, the company image had a positive effecton the employees’satisfaction. Besides, the company image had successfully mediated, in partsand with positive effect, the corporate social responsibility on the employees’ satisfaction.